Serologic test vs antigenemia assay as diagnostic marker for cytomegalovirus infection in children. - Agnes Yunie, Agnes Yunie (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2002)
Objective: To determine the level IgG and IgM anti-CMV in children clinically suspected to be infected by Cytomegalovirus (CMV) and to determine the diagnostic value of IgG dan IgM anti-CMV as diagnostic tools for active CMV infection with antigenemia assay as the gold standard.Material and methods: Diagnostic test, observational cross sectional study. All children suspected to have CMV infection who were hospitalized or who visited neurology outpatient clinic in Sardjito Hospital in March 1" - September 11" 2002 were enrolled in this study. Serologic test for IgG and IgM anti-CM- and antigenemia assay were conducted to confirm the diagnosis of active CMV infection.Results: Nine of 82 specimens (12%) were confirmed to have active CMV. The cut off point of IgG was 265.75 AU/ml, with the sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) of 67% (95% CI: 31-91%), 70% (95% CI: 58-80%), 21% (95% CI: 9-42%), 94% (95% CI: 84-99%), respectively, and likelihood ratio (LR) 4.5. The cut off point of IgM was 0.445, with the sensitivity, specificity, PPV and NPV of 56% (95% CI: 23-85%), 67% (95% CI: 55-77%), 17% (95% CI: 7-37%) and 93% (95% CI: 81-98%), respectively and LR 1.7. There was no significant relation between the level of IgG or IgM above cut off point and antigenemia (p=0.06 and p =0.27). Level of IgG combined with IgM had a significant relation with antigenemia (p 0.04), with the sensitivity 75% (95% CI: 22-99%), specificity 81% (95% CI: 66-91%), PPV 27% (95% CI: 7-61%), NPV 97% (95% CI: 84100%) respectively. LR was 5.3. Most of the children (40 patients) had psychomotor disorder (60%). There was significant relation between trombocytopenia and antigenemia (p =0.04).Conclusions: An increased level of IgM combined with IgG above cut off point is a significant diagnostic tool for active CMV infection. Psychomotor disorder is the clinically sign mostly found in active CMV infection. Thrombocytopenia can be used to detect active CMV infection.Key words: active CMV infection - antigenemia - IgM & IgG anti-CMV - IgM anti-CMV - diagnostic test